Ecology of leaf longevity - Kikuzawa, Kihachiro 1941-; Kikuzawa, Kihachiro; Lechowicz, Martin J.; SpringerLink (Online service). (Tokyo Springer Tokyo, 2011)
Leaf longevity is a fundamental process underlying patterns of variation in foliar phenology and determining the distinction between deciduous and evergreen plant species. Variation in leaf longevity is associated with a wide array of differences in the physiology, anatomy, morphology and ecology of plants. This book brings together for the first time information scattered widely in the botanical literature to provide a clear and comprehensive introduction to the nature and significance of variation in leaf longevity. It traces the development of ideas about leaf longevity from the earliest descriptive studies to contemporary theory of leaf longevity as a key element in the function of leaves as photosynthetic organs. An understanding of variation in leaf longevity reveals much about the nature of adaptation at the whole plant level and provides fundamental insights into the basis of variation in plant productivity at the ecosystem level. The analysis of leaf longevity also provides a process-based perspective on phenological shifts associated with the changing climate. Readers will find this an informative synthesis summarizing and illustrating different views in a readily accessible narrative that draws attention to a central aspect of plant biology.
Electronic reproduction.
Keywords: Leaves; Plants -- Longevity; Plant phenology; Leaves -- Ecology; Electronic books